2007
DOI: 10.1128/mcb.01566-06
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Ubiquitin-Specific Protease 8 for Receptor Tyrosine Kinase Stability and Endocytic Trafficking In Vivo

Abstract: Posttranslational modification by ubiquitin controls multiple cellular functions and is counteracted by the activities of deubiquitinating enzymes. UBPy (USP8) is a growth-regulated ubiquitin isopeptidase that interacts with the HRS-STAM complex. Using Cre-loxP-mediated gene targeting in mice, we show that lack of UBPy results in embryonic lethality, whereas its conditional inactivation in adults causes fatal liver failure. The defect is accompanied by a strong reduction or absence of several growth factor rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
201
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(218 citation statements)
references
References 55 publications
17
201
0
Order By: Relevance
“…Its depletion has more severe effects on the organization of the endocytic pathway that combine to inhibit EGFR downregulation (25,177,218,219). One contributing factor to such defective EGFR trafficking is that USP8 controls the stability of ESCRT-0 components, Hrs and STAM in cells and in conditional knockout mice (185,219). However, for Frizzled receptor (Fz) and Smoothened (Smo), key components of Wingless (Wnt) and Hedgehog signaling pathways, respectively, USP8 plays a negative regulatory role with regard to receptor degradation more akin to that originally proposed for AMSH (153,180,281).…”
Section: B Escrt Dubsmentioning
confidence: 99%
“…Its depletion has more severe effects on the organization of the endocytic pathway that combine to inhibit EGFR downregulation (25,177,218,219). One contributing factor to such defective EGFR trafficking is that USP8 controls the stability of ESCRT-0 components, Hrs and STAM in cells and in conditional knockout mice (185,219). However, for Frizzled receptor (Fz) and Smoothened (Smo), key components of Wingless (Wnt) and Hedgehog signaling pathways, respectively, USP8 plays a negative regulatory role with regard to receptor degradation more akin to that originally proposed for AMSH (153,180,281).…”
Section: B Escrt Dubsmentioning
confidence: 99%
“…There are at least four DUBs-USP8, USP18, AMSH and POH1-that affect the trafficking of RTKs like epidermal growth factor receptor (EGFR), Met and ErbB2. USP8 has an important role in the stabilization of RTKs through deubiquitylation, allowing their recycling to the plasma membrane (Niendorf et al, 2007), although other studies have suggested that USP8 might promote degradation of RTKs (Alwan and van Leeuwen, 2007). In addition, the endosomeassociated AMSH (also known as STAMBP) promotes EGFR recycling at the expense of lysosomal sorting (McCullough et al, 2004;Clague and Urbe, 2006).…”
Section: Signaling Pathwaysmentioning
confidence: 99%
“…and Presenilin 1 Protein Levels-Depletion of USP8 has been shown to decrease protein levels of USP8 substrates, as a result of increased substrate ubiquitination and degradation (23,36). To determine whether USP8 depletion resulted in a decrease in BACE1, we performed siRNA-mediated knockdown of USP8, using two different siRNAs targeting USP8 in an H4 neuroglioma cell line overexpressing BACE1-GFP (H4-BACE1-GFP).…”
Section: Usp8 Depletion Decreases Bace1-gfp But Not Adam10mentioning
confidence: 99%
“…Although some investigators have noted an increase in total cellular EGFR when USP8 is depleted (24,28), others have determined that USP8 depletion leads to an increase in EGFR lysosomal degradation, accompanied by a decrease in EGFR protein levels in both cellular and mouse conditional knock-out models (23,36,37). USP8 has a role not only in protein degradation but also in protein trafficking.…”
mentioning
confidence: 99%
See 1 more Smart Citation